Large influence of dust on the Precambrian climate - Peng Liu (Nature Portfolio, 2020)
Dust emissions are likely to increase significantly when land vegetation is absent, such as during the Precambrian period. Here, the authors use climate simulations to find that high dust emissions in the Precambrian could have cooled the global climate by ~10 °C.